2009
DOI: 10.1002/humu.20822
|View full text |Cite
|
Sign up to set email alerts
|

Ancestry informative marker sets for determining continental origin and admixture proportions in common populations in America

Abstract: To provide a resource for assessing continental ancestry in a wide variety of genetic studies we identified, validated and characterized a set of 128 ancestry informative markers (AIMs). The markers were chosen for informativeness, genome-wide distribution, and genotype reproducibility on two platforms (TaqMan® assays and Illumina arrays). We analyzed genotyping data from 825 subjects with diverse ancestry, including European, East Asian, Amerindian, African, South Asian, Mexican, and Puerto Rican. A comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
474
2
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(496 citation statements)
references
References 40 publications
13
474
2
7
Order By: Relevance
“…These results show that as few as 24 AIMs could determinate similar admixture proportions. This observation was already sustained by Kosoy et al 25 in a similar estimation of ancestry, using 128, 96, 64, 48 and 24 AIMs sets. It is important to remark that in our study, panels of 20 and 14 AIMs were evaluated and the difference found in the mean of proportions for the African component indicates that the minimal quantity of markers useful for admixture estimation is 24 AIMs.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…These results show that as few as 24 AIMs could determinate similar admixture proportions. This observation was already sustained by Kosoy et al 25 in a similar estimation of ancestry, using 128, 96, 64, 48 and 24 AIMs sets. It is important to remark that in our study, panels of 20 and 14 AIMs were evaluated and the difference found in the mean of proportions for the African component indicates that the minimal quantity of markers useful for admixture estimation is 24 AIMs.…”
Section: Discussionsupporting
confidence: 59%
“…6,11,21,23,[25][26][27][28][29][30] The admixture estimates reported in these studies are based on blood groups, serum proteins, STRs and AIMs. As a whole, the data are consistent with the Mexican population history and reflect a gradient with a higher proportion of Native American ancestry in the southern states and increased ancestry of the African contribution in the states of the Gulf of Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…14 The final marker set included 92 single-nucleotide polymorphisms that demonstrated large differences in allele frequency between ancestral populations from Europe, sub-Saharan Africa and America (Supplementary Table S1). …”
Section: Ancestry Informative Markersmentioning
confidence: 99%
“…15) analyses of AIM genotyping results as previously described. 14 The analyses were performed with using representatives of the three parental populations (96 samples each) and under the assumption of three populations (K ¼ 3) and with representatives of the two parental populations (K ¼ 2) under the assumption of two populations.…”
Section: Admixture Assessmentmentioning
confidence: 99%
“…We ensured that there were no ethnic variations by genotyping 24 markers with known allele frequencies in Caucasians (Kosoy et al., 2009). Data for one of these did not pass quality control; for the remaining 23, the minor allele frequencies did not significantly differ from those expected in Caucasians ( p  =   .35).…”
Section: Methodsmentioning
confidence: 99%